2010
DOI: 10.4238/vol9-4gmr981
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in wild genotypes of Passiflora cincinnata based on RAPD markers

Abstract: ABSTRACT. The genetic diversity and characteristics of commercial interest of Passiflora species make it useful to characterize wild germplasm, because of their potential use for fruit, ornamental and medicinal purposes. We evaluated genetic diversity, using RAPD markers, of 32 genotypes of Passiflora cincinnata collected from the wild in the region of Vitória da Conquista, Bahia, Brazil. Thirteen primers generated 95 polymorphic markers and only one monomorphic marker. The mean genetic distance between the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…For some species, such as P. caerulea , P. cincinnata , P. coccinea , and P. setacea , interspecific hybrids are being developed and characterized [33,54,72] and estimates of genetic diversity and confirmation of the hybrids based on molecular markers are being carried out [54,62,63]. …”
Section: Contributions Of Molecular and Genetic Studies For The Chmentioning
confidence: 99%
See 3 more Smart Citations
“…For some species, such as P. caerulea , P. cincinnata , P. coccinea , and P. setacea , interspecific hybrids are being developed and characterized [33,54,72] and estimates of genetic diversity and confirmation of the hybrids based on molecular markers are being carried out [54,62,63]. …”
Section: Contributions Of Molecular and Genetic Studies For The Chmentioning
confidence: 99%
“…The use of RAPD markers has also contributed to estimates of diversity in wild species of passion fruit, such as P. cincinnata , P. nitida , and P. setacea [62,63,81]. In these studies, large genetic variability was observed, with percentages of polymorphic loci ranging from 64% in P. nitida [81] to 93% in P. setacea [63].…”
Section: Contributions Of Molecular and Genetic Studies For The Chmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of molecular markers is fundamentally important for enhancing the amount of information generated and for reducing the time required to obtain results (Ferreira and Rangel 2011). In this context, we note a considerable increase in research devoted to obtaining estimates of genetic variability using molecular markers in both commercial (Ortiz et al 2012;Costa et al 2012;Cerqueira-Silva et al 2010a;Bellon et al 2007;Viana et al 2003) and wild passion fruit species (Cerqueira-silva et al 2010b(Cerqueira-silva et al , c, 2012aJunqueira et al 2007). These studies have identified low variability among commercial accessions of P. edulis and generally wide variability among wild accessions of passion fruit, reinforcing the potential for the use of these materials as a resource in breeding programs.…”
Section: Introductionmentioning
confidence: 99%